Territorial mobility in traditional societies of Bhojpur, Majhkirant (Geographical Journal of Nepal, 2021)
Territorial mobility is an inherent element for survival and it is a common feature of rural area. It reflects the whole life style and livelihood pattern of a community. Therefore, territorial mobility could be an important aspect of living and coping with external world particularly in the traditional communities of rural Nepal. This paper seeks to explore the changing territorial mobility among the Rai people from Sampang area of Bhojpur district in Majhkirant region. The mixed method, both quantitative and qualitative is adopted for data collection. The formal instruments such as household survey, focus group discussion, mobility register, and the folk sources such as folk songs, local sayings, proverbs, local events were used to generate the data together with the observation method as well. Findings indicate that all forms of mobility of Majhkirant people in which they participate can be summarized into two categories i.e. basai sarai and ghumphir. The long-term moves such as Muglan bhasine, Madhesh jharne, ghar khana jane, desh nikala hune are the specific types of basai sarai. On the other hand all types of short-term mobility normally of short distance are part of ghumphir which are common forms of movement among the people of this area. The feature and frequency of various types of moves vary among Rai and non-Rai community and it also differs over time and space. For example, pitri garna jane, nwagi garna jane, mang garna jane, kaliya jane are more noticeable among Rai community while tirthayatra, chardham jane, astu selauna jane, puranma jane, katha sunna jane are commonly found among non-Rai (Brahmin community). Similarly, moves such as, Lahur jane, phukna jane, ghar banauna jane are associated with Rai people whereas moves like jajamani garna jane, puranma jane, katha bhanna jane are primarily confined to Brahmin community. Many other forms of localized moves were also noticed and all of them had their linkages with participation in socio-cultural, professional, political and economic spheres of rural life. Some moves associated with kinship and neighborhood network as well as obligatory are commonly found in all community. In addition, many of these move are age-sex specific, others are associated with occupation of the person and with changing aspiration of people including changing geography of development activities.